METODE PEMBELAJARAN KOSAKATA - Kastam Syamsi, Kastam Syamsi (Jurnal Cakrawala Pendidikan, 2016)
Vocabulary teaching is one of the important aspects of language teaching. Actually, vocabulary teaching is one of the oldest areas of interest in educational research. But, it is not gaining much attention. There are two conlmon types of vocabulary teaching methods, namely, direct and indirect ones. Direct nlethods cover all methods directly presenting vocabulary as instructional material, such as, defi itionanl d contcxlual methods, whercas indirect methods cover various language activities supporting vocabulary teaching, including reading, listening, speaking, and writing. With various research results as basis, it can be concluded that there is no one single method which is the best. Every method has its special characteristics. The teacher should use various methods in teaching vocabulary, while, on the other hand, extensive reading is one of the resources for vocabulary development.